NILAI PENTING KOMPLEKS MAKAM SYEH TUBAGUS ABDULLAH DAN BALUNG TUNGGAL DI KECAMATAN PURBARATU, KOTA TASIKMALAYA - Widyastuti, Endang; Boedi, Oerip Bramantyo (Kemendikbud, 2018)
Site of the tomb of Sheikh Tubagus Abdullah is located in Sukasih Village, Purbaratu, Tasikmalaya City. Sheikh Tubagus Abdullah has historically been regarded as an important figure in the spread of Islam in Purbaratu and beyond. As a site, the complex of this tomb has an important meaning for the community. One benchmark of this measure is to weight the importance of the site. Based on this study aims to obtain a historical picture and the importance of the complex of the tomb. The study begins with collecting data in the field of observation of material objects and interviews with resource persons. Data analysis uses quality parameters and important value parameters. Based on the results of data analysis obtained conclusion that this site has a high value of high importance. Keywords: important value, complex of tomb of Sheikh Tubagus Abdullah, Purbaratu, Tasikmalaya City